Respuesta :

[tex]\dfrac{\mathrm dz}{\mathrm dt}=\dfrac{\partial z}{\partial x}\dfrac{\mathrm dx}{\mathrm dt}+\dfrac{\partial z}{\partial y}\dfrac{\mathrm dy}{\mathrm dt}[/tex]
[tex]\dfrac{\mathrm dz}{\mathrm dt}=(y^9-2xy)(2t)+(9xy^8-x^2)(2t)[/tex]
[tex]\dfrac{\mathrm dz}{\mathrm dt}=20t^{19}-144t^{17}+432t^{15}-672t^{13}+504t^{11}-336t^7+282t^5-112t^3+18t[/tex]

The value of dz/dt using the chain rule is [tex]2t[(t^2-1)^9 -2(t^4-1)]+2t[9(t^2+1)(t^2-1)^8-(t^2+1)^2][/tex]

According to chain rule:

[tex]\frac{dz}{dt} = \frac{\delta z}{\delta x} \frac{dx}{dt} + \frac{\delta z}{\delta y} \frac{dy}{dt}[/tex]

Given the following expressions

z = xy⁹ − x²y,

x = t² + 1

y = t² − 1

Get the differentials in the equation

[tex]\delta z/\delta x = y^9-2xy\\dzx/dt = 2t\\\delta z/\delta y =9xy^8-x^2\\dy/dt = 2t[/tex]

Substitute the differentials into the formula

[tex]\frac{dz}{dt} = (y^9-2xy)(2t)+(9xy^8-x^2)(2t)\\\frac{dz}{dt} = 2t[(t^2-1)^9 -2(t^4-1)]+2t[9(t^2+1)(t^2-1)^8-(t^2+1)^2][/tex]

Hence the value of dz/dt using the chain rule is [tex]2t[(t^2-1)^9 -2(t^4-1)]+2t[9(t^2+1)(t^2-1)^8-(t^2+1)^2][/tex]

Learn more here: https://brainly.com/question/22882675